Disparities in self-reported exposure to tobacco marketing among youth and young adults from low-socioeconomic status neighbourhoods in Mexico City - Qinghua Nian; Graziele Grilo; Joanna E. Cohen; Katherine C. Smith; Luz Myriam Reynales-Shigematsu; Maria Guadalupe Flores Escartin; Meghan B. Moran (Global Public Health, 2023)
ABSTRACTExposure to tobacco marketing is positively associated with smoking initiation and behaviours. There is limited literature examining disparities among reported exposure in low- and middle-income countries. This study sought to fill this gap with a survey among 1427 adolescents and 889 adult smokers in Mexico City in 2020. Data were analysed using chi-square and hierarchical regression models. Two-thirds of adolescents noticed cigarette pack displays in stores. Participants from low- and mid-socioeconomic status (SES) neighbourhoods were more exposed to tobacco marketing than their counterparts through several channels. After addressing the shared variance among participants from the same household nested in neighbourhood SES level and controlling for gender, adolescent non-smokers and adult smokers who noticed pack displays were more likely to be susceptible to smoking (OR = 1.8, 95% CI 1.4–2.4) and to smoke more (OR = 1.7, 95% CI 1.21–2.47); adult smokers who noticed tobacco marketing at more places were less likely to be certain about smoking risks (OR = 0.9, 95% CI 0.8–0.9). The results suggest that the tobacco industry targets youth and individuals from low-SES neighbourhoods through several channels. Greater exposure to tobacco marketing was associated with increased susceptibility to smoking and decreased risk perception. These findings support a comprehensive ban on tobacco marketing in Mexico.